Entrepreneurial Spirit Development of Female Students of the Islamic College Siti Aisyah Malang Dormitory through Assistance in the Production of Processed Livestock Products - Apriliana Devi Anggraini; Septi Nur Wulan Mulatmi; Nimas Rizky Fauziyyah (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2023)
Increasing the entrepreneurial spirit in female students need to be done to stimulate entrepreneurial motivation, develop and create new innovations so they are able to improve their skills and become independent student after completing their study. Islamic College Siti Aisyah is a dormitory for 20 female students with an age range of 18- 23 years managed by Regional Aisyah Malang. This activity aims to improve understanding of livestock products, improve skills manufacture of processed livestock products, and provided stimulus to increase entrepreneurial spirit. Implementation of community service activities was socialization, training, and assistance in making pasteurized milk and chicken nugget for four months. Questionnaires ware given to students before and after training. The data analyzed used quantitative descriptive. This activities had resulted in processed products in the form of chicken nuggets and pasteurized milk with several modified variants. In conclusion, this activities were increased in understanding of livestock products and processed products by 70%. In addition, this activities can stimulate entrepreneurial motivation about 5% of participants applied this activity independently and they got benefit from it